posted by Nathan .
If the coefficient of the x^2 term is 1 and the middle term coefficient is even, I use completing the square rather than the formula
x^2 - 6x + ... = -13 + ....
x^2- 6x + 9 = -13+9
(x-3)^2 = -4
x-3 = ±√-4
x = 3 ± 2i
In google type:
quadratic equation online
When you see list of results click on:
Free Online Quadratic Equation Solver:Solve by Quadratic Formula
When page be open in rectangle type:
x ^ 2 - 6 x + 13 = 0
and click option: solve it!
You wil see solution step-by-step